Blockade of Neutrophil’s Chemokine Receptors CXCR1/2 Abrogate Liver Damage in Acute-on-Chronic Liver Failure - Khanam, Arshi; Trehanpati, Nirupma; Riese, Peggy; Rastogi, Archana; Guzman, Carlos Alberto; Sarin, Shiv Kumar (Frontiers in Immunology, 2017)
BACKGROUND: Neutrophils serve as critical players in the pathogenesis of liver diseases. Chemokine receptors CXCR1 and CXCR2 are required for neutrophil chemotaxis to the site of inflammation/injury and are crucial in hepatic inflammatory response. However key mechanism of neutrophil mediated liver injury in acute-on-chronic liver failure (ACLF) remains highly elusive; which could be targeted for the development of new therapeutic interventions. METHODS: To demonstrate the role of CXCR1/CXCR2 expressing neutrophils in hepatic injury, we investigated CXCR1/CXCR2 receptor expression in 17 hepatitis B virus (HBV)-related ACLF patients in comparison to 42 chronic hepatitis B (CHB) and 18 healthy controls (HC). Mechanism of neutrophil mediated cell death was analyzed by in vitro co-culture assays and correlated with the patient data. In addition, to find out any etiological based variations in ACLF, 19 alcohol-related ACLF patients were also included. RESULTS: In ACLF, neutrophils have high expression of CXCR1/CXCR2 receptors which potentially participate in hepatocyte death through early apoptosis and necrosis in contact dependant and independent mechanisms. Importantly, blockade of CXCR1/CXCR2 with SCH 527123 antagonist significantly reduced cell death by targeting both the mechanisms. No etiology based differences were seen between ACLF groups. Importantly, absolute neutrophil count (ANC) was particularly higher in clinically severe ACLF patients and non-survivors (p<0.0001). Multivariate analysis demonstrated ANC and CXCL8/IL-8 as a predictor of mortality. Further receiver operating characteristics curve confirmed the cut-off of ANC >73.5% (sensitivity:76.5% and specificity:76.5%) and CXCL8/IL-8 >27% (sensitivity:70% and specificity:73%) in prediction of mortality. CONCLUSION: Blockade of CXCR1/CXCR2 diminished the production of inflammatory mediators and reduced cell death; therefore pharmacological neutralization of CXCR1/CXCR2 could provide novel therapeutic target in the management of ACLF.